1998
DOI: 10.1111/j.1524-4725.1998.tb04221.x
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of pH and Concentration in Lactic Acid-induced Stimulation of Epidermal Turnover

Abstract: The desquamative and proliferation-stimulating effects of lactic acid are very pH and concentration dependent, suggesting the "free acid" concentration is the active moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…The GA tested in the present study is one of the AHA used for chemical peeling, and the effects of AHA have been reported to be dose‐ and pH‐dependent (24). Because CD activity is pH‐dependent and optimum at around pH 3, it is possible that it is activated by acidification of the stratum corneum following application of acidic agents, including other AHA and acidifying agents, as long as they meet the optimal pH for CD, though additional study is required.…”
Section: Discussionmentioning
confidence: 99%
“…The GA tested in the present study is one of the AHA used for chemical peeling, and the effects of AHA have been reported to be dose‐ and pH‐dependent (24). Because CD activity is pH‐dependent and optimum at around pH 3, it is possible that it is activated by acidification of the stratum corneum following application of acidic agents, including other AHA and acidifying agents, as long as they meet the optimal pH for CD, though additional study is required.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous factors influencing SC acidification include the generation of free fatty acids from phospholipid hydrolysis catalysed by secretory phospholipase A2 and the sodium/hydrogen exchanger isoform 1 (NHE1), which is expressed in the outer nucleated layers of the epidermis [3]. Exogenous mechanisms include the generation of free fatty acids by bacterial lipase and free fatty acids derived from sebum and eccrine gland‐derived products [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the last pathway is currently under discussion 26 . In addition, exogenous mechanisms such as the eccrine gland‐derived lactic acid 27,28 and the free fatty acids of pilosebaceous origin 29,30 may also contribute to skin surface acidification. None of these potential mechanisms has previously been linked to the formation of an acidic skin pH in human newborns 31,32 …”
mentioning
confidence: 99%